GANGGUAN KESEIMBANGAN SEBELUM DAN SETELAH PEMBERIAN AIR KELAPA HIJAU (Cocos nucifera L) PADA PEKERJA PENGECATAN YANG TERPAPAR TIMBAL (Pb) DI INDUSTRI KAROSERI SEMARANG - Benedikta Familia Santcawarti; Onni Setiani; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Painting process in the industry carrosserie at Semarang caused of workers exposed to lead. The impact of lead exposure is continuously on of which is the destruction of the myelin sheath of axons that cause postural muscle responses that can not work synergistically to maintain body balance. The purpose of this study was to determine the difference in balance disorders before and after green coconut water (Cocos nucifera L) supplementation to the painting workers exposed to lead in industrial carroserrie at Semarang. This study was a quasi experiment with experiment design. The population in this study was all painting workers in carrosserie factory at Semarang who were included in inclusion criteria. Collecting data used tool such as questioner. Lead examination in the blood was measured by AAS (Atomic Absorption Spectrophotometer), and for body balance disorders were measured by Romberg test. A total of 14 workers (43,8%) had impaired balance before supplementation the green coconut water (Cocos nucifera L). Then after supplementation of green coconut water (Cocos nucifera L) workers who experienced impaired balance as much as 8 workers (25%). The result of wilcoxon test showed that there was a difference between before and after giving of green coconut water (Cocos nucifera L) with body balance disorders to painting workers in carrosserie factory (p value = 0.014). In conclusion, there was a difference between before and after giving of green coconut water (Cocos nucifera L) with body balance disorders.